Development of the acoustic startle response in rats and its change after early acoustic trauma - Rybalko, Natalia; Chumak, Tetyana; Bureš, Zbyněk; Popelář, Jiří; Šuta, Daniel; Syka, Josef (Behavioural brain research, 2015)
Even brief acoustic trauma during the critical period of development that results in no permanent hearing threshold shift may lead to altered auditory processing in adulthood. By monitoring the acoustic startle response (ASR), we examined the development of auditory function in control rats and in rats exposed to intense noise at the 14th postnatal day (P14). First ASRs appeared on P10-P11 to intense low-frequency tones. By P14, the range of sound intensities and frequencies eliciting ASRs extended considerably, the ASR reactivity being similar at all frequencies (4-32 kHz). During the subsequent two weeks, ASR amplitudes to low-frequency stimuli (4-8 kHz) increased, whereas the ASRs to high-frequency tones were maintained (16 kHz) or even decreased (32 kHz). Compared to controls, noise exposure on P14 (125 dB SPL for 8, 12, or 25 min) produced transient hyper-reactivity to startle stimuli, manifested by a decrease of ASR thresholds and an increase of ASR amplitudes. ASR enhancement occurred regardless of permanent hearing loss and was more pronounced at high frequencies. The hyper-reactivity of ASRs declined by P30; the ASR amplitudes in adult exposed rats were lower than in controls. The histological control did not reveal loss of hair cells in adult exposed rats, however, the number of inner hair cell ribbon synapses was significantly decreased, especially in the high-frequency part of the cochlea. The results indicate that early acoustic trauma may result in complex changes of ASRs during development.
Keywords: Hearing Tests; synapse; Evoked Potentials, Auditory, Brain Stem; Auditory system; Noise exposure; sluchové testy; Acoustic Stimulation; Female; Reflex, Startle; Rat; senzorické prahy; Auditory Perception; Cochlea; Development; zvířata; kochlea; sluchové kmenové evokované potenciály; Critical period; Rats, Long-Evans; úleková reakce; Sensory Thresholds; ženské pohlaví; potkani Long-Evans; Acoustic startle reflex; Animals; Synapses; sluchová percepce; akustická stimulace